1983
DOI: 10.1002/j.1460-2075.1983.tb01716.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of transfer and stabilization of Agrobacterium DNA in plant cells

Abstract: In an attempt to elucidate the transfer and integration mechanism of Agrobacterium DNA upon crown gall induction, we translocated a borderless T‐DNA to different sites of the C58 Ti plasmid. As a result of the physical linkage of the T‐DNA onc genes with other Ti plasmid functions, the concerned strain retained tumor‐inducing capacity. However, when the borderless T‐DNA is separated on an independent replicon while all other pTi functions are provided in trans, the strain can no longer induce tumors on plants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…In contrast mutants that lack the left border repeat can still efficiently transfer the onc-genes to the plant cell (13,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast mutants that lack the left border repeat can still efficiently transfer the onc-genes to the plant cell (13,21).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the border fragments of the T-region showed that a deletion of the left border repeat did not result in any detectable effect on the T-region transfer process (13,21), while deletion of the right border of the nopaline T-region (35) and of the octopine T-region (30) resulted in the loss of oncogenicity. The onc-genes and the vir-genes essential for tumor induction were still intact in these deletion mutants.…”
Section: N a Isolation Proceduresmentioning
confidence: 99%
“…Because T-DNA transfer is apparently a polar process, initiating at the right border and continuing to (and perhaps beyond) the left border (Caplan et al, 1985;Joos et al, 1983;Miranda et al, 1992;Peralta et al, 1986), we expected that plants generated using pBSG-t w o u l d have a higher probability of receiving and integrating the mas2'-gusA gene than would plants generated using pBSG-2. Our data, however, indicated that there was no major difference in the transfer of the gusA gene whether this gene were located close to the left or to the right T-DNA border.…”
Section: Identification Of T-dna and Binary Vector 'Backbone' Single-mentioning
confidence: 99%
“…Deletion of the right-hand border repeat abolishes tumorigenesis (23,32,37,43,55); in contrast, removal of the left border does not detectably affect virulence (31,38). Inversion of the rightborder repeat in the Ti plasmid severely attenuates tumorigenesis, indicating that orientation affects its activity (37,55).…”
mentioning
confidence: 99%